MDM2 (T309G) Gene Polymorphism Determines the Susceptibility of Hepatocellular Carcinoma in Bangladesh - Hosen, Md. Bayejid; Khaleque, Narwana; Chakraborty, Sajib; Mahtab, Mamun Al; Kabir, Yearul (Asian Pacific Journal of Cancer Biology, 2021)
Background: Hepatocellular carcinoma (HCC) is one of the fatal cancer types worldwide, and a variety of genetic factors are considered to be associated with this incidence. MDM2 gene plays a pivotal role in various pathways, which are essential to combat tumor formation. The study aimed to find out the associations of MDM2 (T309G, rs2279744) gene polymorphism with the development of HCC in the Bangladeshi population. Methods: A case-control study on 100 HCC patients and 110 control subjects was conducted. The genotyping of the MDM2 (T309G) gene was done using PCR-RFLP methods. Results: The percentage of TT and GG genotypes were significantly different (p<0.01) among the study subjects. There were four genotyping groups, while the subjects with TT genotypes were considered the reference group. Patients with GG genotypes were at high risk of developing HCC (OR, 3.6; 95 % CI, 1.64–7.80; p<0.01) compared to the control. On the other hand, the association of TG genotypes with HCC was not statistically significant (OR, 1.8; 95 % CI, 0.91–3.40, p>0.05). In addition, patients having either GG or TG genotypes showed higher risk for HCC compared to control group (OR = 2.20; 95% CI = 1.21–4.14; P < 0.05). Conclusion: Our study suggested that the MDM2 gene may have a strong association with the development of HCC, and the GG allele could serve as an essential determinant to identify the higher risk of HCC in the Bangladeshi population.